Object of defects of vacancy type in graphene plane into clusters and the influence of vacancy clusters on morphology and electronic properties of structure - V. A. Sachkov (Омский научный вестник)
This work is devoted to the study of the effect on the morphology and on the electronic properties of the graphene plane of defects of the vacancy type in the form of a vacancy cluster, depending on the size of the cluster. The optimal configurations of the arrangement of carbon atoms for the graphene plane from vacancy clusters are found. The electronic band structure is calculated for them. The calculations are performed by the ab initio method. The analysis of the dependence of the morphology of the structure and some parameters of the electronic structure on the size of the vacancy cluster is carried out. The results obtained are applicable to the analysis of the band structure of single-walled carbon tubes containing vacancy-type defects.